2010
DOI: 10.1128/aem.00595-10
|View full text |Cite
|
Sign up to set email alerts
|

Thaumarchaeal Ammonia Oxidation in an Acidic Forest Peat Soil Is Not Influenced by Ammonium Amendment

Abstract: Both bacteria and thaumarchaea contribute to ammonia oxidation, the first step in nitrification. The abundance of putative ammonia oxidizers is estimated by quantification of the functional gene amoA, which encodes ammonia monooxygenase subunit A. In soil, thaumarchaeal amoA genes often outnumber the equivalent bacterial genes. Ecophysiological studies indicate that thaumarchaeal ammonia oxidizers may have a selective advantage at low ammonia concentrations, with potential adaptation to soils in which minerali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
137
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(149 citation statements)
references
References 52 publications
9
137
3
Order By: Relevance
“…Soil AOB gene sequences were significantly amplified and detected from two of fifteen soil samples, despite using the FastDigest ® Mbo I enzyme, a procedure that was successfully applied to the typical steppe soils in northern China [34]. Other studies reported that AOB was not detected in the acidic forest soils, either [33,36]. This is partly attributed to the low soil pH in the subtropical region (Fig.…”
Section: Unamplified Aob Populationmentioning
confidence: 83%
See 1 more Smart Citation
“…Soil AOB gene sequences were significantly amplified and detected from two of fifteen soil samples, despite using the FastDigest ® Mbo I enzyme, a procedure that was successfully applied to the typical steppe soils in northern China [34]. Other studies reported that AOB was not detected in the acidic forest soils, either [33,36]. This is partly attributed to the low soil pH in the subtropical region (Fig.…”
Section: Unamplified Aob Populationmentioning
confidence: 83%
“…Theoretically, the decrease in soil pH caused by N additions reduces soil NH 3 availability because of the formation of ionized NH 4 þ [51,52]. The concentration of ammonia substrate in soils is considered below the growth threshold of cultured AOB in soil when pH is below 4.5, and this is in turn favorable to the growth of high-affinity AOA community [33,50]. Soil pH at all treatment plots was below 4.5 (Fig.…”
Section: Effects Of N Addition On Ammonia-oxidizer Communitiesmentioning
confidence: 99%
“…A majority of acidic soils selected higher AOA abundance over AOB (Leininger et al, 2006;He et al, 2007) implying a strong ability of AOA ecotypes adapting to low-pH soils. Moreover, high nitrification rates were presumably associated with growth of AOA in an acidic forest soil in the absence of AOB (Stopnisek et al, 2010), and a significant correlation between AOA community abundance and nitrification potential was observed in Chinese acidic tea orchard soils (Yao et al, 2011). In addition, physiological and genomic studies of the first isolate AOA, Nitrosopumilus maritimus, demonstrated a low-level ammonia substrate threshold that was significantly lower than the requirement by cultivated AOB (Martens-Habbena et al, 2009), and significantly divergent pathways of ammonia oxidation from AOB offering ecological advantage in ammonia-limited environments (Walker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is currently unclear whether their competitive strength and ammonia oxidation activity varies depending on the availability of ammonium. Field and microcosm studies show either enhanced abundance and activity of AOA or inhibition in response to nitrogen (N) fertilization (Di et al, 2009;Stopnisek et al, 2010;Pratscher et al, 2011;Verhamme et al, 2011;Levicnik-Hofferle et al, 2012;Ke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%